(untitled) (Przegląd Religioznawczy – The Religious Studies Review, 2020)
The Evangelical Church of the Augsburg Confession in interwar Poland faced a cultural split between German-speaking members, who were overwhelming in number, and Polish patriots, who wanted to integrate the church in the Polish state. This conflict had a great impact on church policy and was reflected in the press discourse, which is briefly presented in the article.